Suitability Mapping for Broiler Closed House Farm Using Analytical Hierarchy Process and Weighted Overlay with Emphasize on Environmental Aspects - Wijayanto, Arif Kurnia; Seminar , Kudang Boro; Afnan, Rudi (International Journal of Poultry Science, 2015)
Massive development of broiler farms has led to many socio-environmental problems. A mapping based on the socio-environmental factors and sustainable principles is urgently needed to cope with this problem. The objective of this research was to create a suitability map for broiler farm development in Parung region, Indonesia-as study area. There were four factors considered in the mapping: (1) ecology and environmental impact, (2) economic and infrastructure, (3) natural condition and (4) natural disaster vulnerability, each of which consists of sub-factors. An Analytical Hierarchy Process (AHP) by using pairwise comparison method was applied to determine weight of each factor and sub-factor based on experts’ valuation. From the AHP process, natural condition was considered as the most important factor, followed by ecological and environmental impact factor. By considering weights resulted from the AHP, the spatial analysis and weighted overlay by GIS software were applied in the data processing and suitability map building. Suitability map for broiler farm in Parung region has been created and can be used as guidance for broiler farm development and also for local government as decision support tool to manage the farming area concerning ecology and environment factor.